Neurobiological bases of reading disorder Part I: Etiological investigations. Issue 4 (April 2017) - Xia, Zhichao; Hancock, Roeland; Hoeft, Fumiko
Abstract: While many studies have focused on identifying the neural and behavioral characteristics of decoding‐based reading disorder (RD, aka developmental dyslexia), the etiology of RD remains largely unknown and understudied. Because the brain plays an intermediate role between genetic factors and behavioral outcomes, it is promising to address causality from a neural perspective. In the current study, Part I of the two‐part review, we discuss neuroimaging approaches to addressing the causality issue and review the results of studies that have employed these approaches. We assume that if a neural signature were associated with RD etiology, it would (a) manifest across comparisons in different languages, (b) be experience independent and appear in comparisons between RD and reading‐matched controls, (c) be present both pre‐ and post‐intervention, (d) be found in at‐risk, pre‐reading children, and (e) be associated with genetic risk. We discuss each of these five characteristics in turn and summarize the studies that have examined each of them. The available literature provides evidence that anomalies in left temporo‐parietal cortex, and possibly occipito‐temporal cortex, may be closely related to the etiology of RD. Improved understanding of the etiology of RD can help improve the accuracy of early detection and enable targeted intervention of cognitive processes that are amenable to change, leading to improved outcomes in at‐risk or affected populations.